A Qualitative Study of Job Placement Provider Decisions in Vocational Rehabilitation. (October 2014) - Fleming, Allison R.; Phillips, Brian N.; Kaseroff, Ashley; Huck, Garrett E.
A modified consensual qualitative research approach was taken to determine factors that influence job placement services in selected state Vocational Rehabilitation agencies. Thirty-five counselors, supervisors, and administrators participated in semistructured interviews on job placement and how they determine whether the counselor or another professional (e.g., in-house placement specialist, community rehabilitation provider) provides the direct service. Results indicated that several factors were noted by at least half of the participants, including anticipated intensity of services needed by the client, counselor caseload size/available time, existing employer relationships, availability of a placement service provider, and placement skills. Results highlight the impact of consistently high client volume on placement services, particularly for individuals with the most significant disabilities. Implications related to the current state of policy and practice for placement services, as well as potential future directions, are discussed.